Farmer perception of soil erosion and investment in soil conservation measures: emerging evidence from northern Taraba State, Nigeria - Yusuf, M.B.; Mustafa, F.B.; Khairulmaini, O.S. (CAB International Publishing, 2017)
To combat soil erosion in the northern part of Taraba State, Nigeria, farmers are of major importance. Their perceptions vitally influence the levels of support and investment associated with solving problems of soil erosion through adoption of practices that are alternative to those in current use, including approaches focused on soil conservation. The objective of this study was to evaluate how farmer perceptions of soil erosion influence their investments in soil conservation, particularly soil or stone bunds, their applications of organic amendments and inorganic fertilizers and other soil conservation practices. In the study area, we undertook a field plot experiment and carried out a survey, using open- and closed-ended questions. Water erosion and depletion of fertility were taken as the main indicators of soil erosion. The results of the experiment showed that farmers were aware of and perceived both indicators as having increased over the past decade. Farmer investments in water erosion control (3.7 US/ha) and the prevention of soil fertility depletion (37.8 US/ha) in the study area were found to be limited. The results also showed that awareness of water erosion was only marginally correlated with investment in water erosion control (χ2 = 4.906, P = 0.09) and not associated with investments in soil fertility control measures (χ2 = 0.175, P = 0.92). Those farmers who identified depletion of soil fertility as a problem, based on erosion, were not significantly more likely to make greater investments in soil conservation (χ2 = 0.947, P = 0.62) but did invest more in fertility measures (χ2 = 3.199, P = 0.20). Hence, further research is needed to determine other factors that may influence farmer investment in soil conservation, especially factors related to socio-economic characteristics of farm households, institutional and technological innovations and field characteristics that were not addressed in this study.